Analisis Fungsi Fukujoshi Dalam Anime Captain Tsubasa 2018 - Gusmayanti Gusmayanti; Rita Arni (Universitas Negeri Padang, 2023)
Fukujoshi is a particle that connects the previous words with the words in the next section. Fukujoshi can be found in various media, for example in textbooks, manga, drama, and anime. Fukujoshi has various functions and meanings. In one sentence fukujoshi there are several different functions. Researchers assess the importance of research that analizis fukujoshi in anime, so that there is no misunderstanding of students. The purpose of this research is to find out what are the functions of fukujoshi in the anime Captain Tsubasa 2018.The research design used is a qualitative research with descriptive method. The data in this study are sentences that use the fukujoshi function in the anime Captain Tsubasa 2018 based on the theory of Chandra (2009). The source of data in this study is the anime Captain Tsubasa 2018. The instrument of this research is the researcher himself. Based on the results of the research conducted, the researchers found 2 functions of fukujoshi bakari, 2 functions of fukujoshi dake, and 2 functions of fukujoshi hodo in the anime Captain Tsubasa 2018 by Youichi Takahashi based on Chandra's theory (2009).